Increasing competitiveness of fishery products in supporting the achievement of village SDGSs through participatory and innovative programs in Bone Pantai district, Bone Bolango regency - Erlansyah Erlansyah; Emiliyan Mamuki; Mukhlisnah Djalil; Rustam Anwar (Fisheries and Society, 2021)
Tihu Village, located in Bone Pantai district, is one of the coastal villages of Tomini Bay where Tihu village is a village that has abundant fishery potential, but has not been utilized optimally. Through community service programs, community empowerment is carried out, especially mothers to utilize fish potential for into processed products that can support the welfare of the community. The purpose of this activity is to provide training to mothers with participatory learning techniques and direct practical assistance in the field. The method applied in the implementation of service activities in Tihu Village is through training methods with participatory learning techniques and direct practice of processing fish into odeng or Korean fish cake. The output of this activity is the creation of processed fish products in the form of odeng or Korean fish cake. The long-term target is that processed fish products can be an alternative source of livelihood that can improve the community's economy.